Evolution of ecosystems in a forest-savannah mosaic context and human presence since 9000 years BP in Lopé National Park (Central Gabon) : palynological approach - (:unkn) unknown (My University, 2021)
This thesis has studied, mainly using pollen analyzes, the evolution of forest-savanna mosaic vegetation of the Lopé National Park (LNP, Central Gabon), in Central Atlantic Africa. The results of the pollen rain from surface samples of marshes, disseminated within the park, showed (i) the robustness of these marsh deposits in recording the main plant formations of the park; and (ii) highlighted the local to regional signal of these marshes which register very little extra-local vegetation, as the Poaceae which never exceed 25%. In addition, fossil records reveal that this extra-local vegetation, mainly savannah, has been present for at least 9000 years BP at LNP, which shows that these enclosed savannas are much older than their documented establishment in the region. These savannas, which would be relics of an ancient arid period, made an incursion into the forest block around 3800 years BP, following a drop in the humidity of the environment, before a permanent installation of the Poaceae and Cyperaceae within marshes around 3000 years BP, giving them a local signal until today. This colonization of the marshes by the Poaceae was probably due to the opening of the forest block of Central Africa, documented between 3000 and 2000 years BP. The open marshes have been regularly invaded by the nearby riparian forest according to variations in humidity while the forest sites have remained relatively stable for 2000 years BP due to a less sensitivity to changes in humidity. It emerges from the above that Man does not seem to have significantly impacted the evolution of the forest-savannah mosaic of Lopé, although he has had a lasting interaction with this environment. Indeed, the monitoring of the evolution of species of human affinity in the pollen spectra does not show any significant variation both when humans are present in the environment and when they are absent during the hiatus of human occupation ( 1400-800 years BP). The results show that these
Keywords: African Research